Impact Assessment of Small Scale and Illegal Mining Activities – A Case Study of Birim River in Kyebi, East Akim Municipality - Gyampoh, Obiri Alexander (2013)
A Thesis submitted to the Department of Theoretical and Applied Biology, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Master of Science in Environmental Science, May-2013